2017
DOI: 10.17576/3l-2017-2304-01
|View full text |Cite
|
Sign up to set email alerts
|

Not Quite What It Seems: Rethinking the Way We View Teachers’ Beliefs and Practices – A Case Study of a Malaysian ESL Teacher

Abstract: Research has shown that there is high congruity between pedagogical beliefs and classroom practices among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In the context of the current study, identity is explored using a combination of self-constructed metaphors and the role she plays in language teaching. Although Jerome and Samuel (2017) found that their participant's role as a facilitator converges with her classroom practices, their finding lacks clarity regarding TEYL teacher identity. Hence, it is valuable to discover teacher's experience and understand the voice of those who are directly involved in teaching English to young learners.…”
Section: The Participant and Research Contextmentioning
confidence: 89%
“…In the context of the current study, identity is explored using a combination of self-constructed metaphors and the role she plays in language teaching. Although Jerome and Samuel (2017) found that their participant's role as a facilitator converges with her classroom practices, their finding lacks clarity regarding TEYL teacher identity. Hence, it is valuable to discover teacher's experience and understand the voice of those who are directly involved in teaching English to young learners.…”
Section: The Participant and Research Contextmentioning
confidence: 89%
“…Teachers play a significant role in shaping students' motivation in the learning process. According to the study by Jerome and Samuel (2017), experienced teachers have the ability to be more sensitive to the needs and wants of students in the classroom when compared to new teachers. Podolsky et al (2019) in their study found a positive relationship between the length of a teacher's experience and the level of student achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the issue of using L1 in the L2 classroom has not been discussed openly among L2 teachers, their actual classroom practice regarding the L1 use is reportedly to be different (Engku Haliza et.al 2013). Time constraint and teaching experience may have direct influence over teachers' teaching practice including the use of L1 during the lessons (Jerome 2017). Farrel (2019) stated that there are studies that reveal teachers' stance towards L1 is contrary to their language use in the classroom (Tsagari & Georgiou 2016;Alrabah, Wu, Alotaibi & Aldaihani 2016;Imran and Wyatt 2015).…”
Section: Micro-functions Of L1 In the L2 Classroommentioning
confidence: 99%